Evaluation of a variable rate fertilizer application system adpted to coffee crop - de Barros, Murilo Machado; Volpato, Carlos Eduardo Silva; Silva, Flávio Castro da; Palma, Marcos Antônio Zambillo; Spagnolo, Roger Toscan (Coffee Science - ISSN 1984-3909, 2015)
An extremely important factor in the production of coffee and other crops is the distribution of fertilizers on the soil, because the efficient use of this technique may increase productivity, reduces production costs and environmental impacts. Precision Agriculture is an important tool to be used, that aids the achievement of localized and rational application of fertilizers, increasing the management activities. The aim of this research was to evaluate the operational performance of a fertilizer application system at variable rate and to create evaluation parameters for coffee crop. Three types of tests were performed: The Cross-Deposition Test, in order to determine the machine’s maximum distribution range and to observe the effects of speed and doses changes; The Longitudinal Deposition Test, in order to determine the machine’s distribution characteristics along the displacement line, and analyze the application behavior on both sides of distribution; The Work Regime Test in order to check the distribution behavior of the machine in real field conditions. We observed that the variation of doses and speeds haven’t affected the precision of the distribution system. There was variation at the system’s application between right and left sides. The system application at variable rate in real field conditions showed a mean error of -3.31%. Therefore, the methodology used is possible to evaluate the variables present in the fertilizers application in coffee production.